2007
DOI: 10.1074/jbc.m700547200
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium-binding C-terminal Domain of Escherichia coli α-Hemolysin Is a Major Determinant in the Surface-active Properties of the Protein

Abstract: However, the C-terminal domain by itself is devoid of membrane lytic properties. The present results can be interpreted in the light of our previous studies that involved in receptor binding a peptide in the C-terminal region of HlyA. We had also shown experimentally the distinction between reversible membrane adsorption and irreversible lytic insertion of the toxin. In this context, the present data allow us to propose that both major domains of HlyA are directly involved in membrane-toxin interaction, the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 30 publications
1
45
0
3
Order By: Relevance
“…However, the precise role of these sequences in RTX toxin secretion remains elusive (56,57,63). It has been proposed that RTX repeats may promote folding into a functional conformation in the presence of calcium (53), and it has been shown that calcium binding by the RTX repeats induces a stable protein conformation (58,64). However, in the absence of the RTX sequences, LapA presumably is still able to fold and function to some degree, given that a strain carrying a LapA variant lacking the RTX sequences is still capable of biofilm formation on both hydrophobic and hydrophilic substrates.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise role of these sequences in RTX toxin secretion remains elusive (56,57,63). It has been proposed that RTX repeats may promote folding into a functional conformation in the presence of calcium (53), and it has been shown that calcium binding by the RTX repeats induces a stable protein conformation (58,64). However, in the absence of the RTX sequences, LapA presumably is still able to fold and function to some degree, given that a strain carrying a LapA variant lacking the RTX sequences is still capable of biofilm formation on both hydrophobic and hydrophilic substrates.…”
Section: Discussionmentioning
confidence: 99%
“…One calcium ion binds each repeat, and binding causes the formation of a "spring-like" betasuperhelix structure (Baumann et al, 1993). These repeats have recently been shown also to play a role in interaction with the host cell surface (Sanchez-Magraner et al, 2007), and LtxA has been reported to have 12 such repeats (Kraig et al, 1990). At the extreme C-terminus is a ~100-amino-acid domain that is involved in secretion of the toxin by a type I secretion system (discussed below).…”
Section: Rtx Toxinsmentioning
confidence: 99%
“…At all events, the interaction of HlyA with a target-cell membrane devoid of any specific proteinaceous receptor appears to occur in two steps: an initial reversible adsorption of the toxin that is sensitive to electrostatic forces followed by an irreversible membrane insertion (Bakás et al, 1996), (Ostolaza et al, 1997). Studies with the isolated calcium-binding domain of HlyA revealed that that part of the protein may be adsorbed onto the membrane during the early stages of HlyA-membrane interaction (Sanchez-Magraner et al, 2007). The next step in the hemolytic process is the insertion of the toxin into the membrane.…”
Section: The Mechanism Of Action Of Hlyamentioning
confidence: 99%